The Capacity of Barangays in Participatory Rural-Urban Planning and Localizing the SDGs: Evidence from Kolambugan, Lanao del Norte, Philippines - Christian Jeiel Partosa; Jack B Isolana; Maria Pia M Sison; Perla P Palomares (Internasional Journal of Politics and Public Policy, 2026)
Barangay Local Government Units (BLGUs) play a vital role in localizing the United Nations Sustainable Development Goals (SDGs) at the grassroots level. This study looks into the capacity of selected barangays in the Municipality of Kolambugan, Lanao del Norte namely Baybay, Libertad and Poblacion, in the realms of participatory rural-urban planning and SDG awareness. Using a mixed-methods research design, data were gathered through surveys, focus-group discussions, and document review and focused on local planning practices, the participation of the stakeholders and SDG awareness. Results show that the level of community involvement is strong as Libertad (4.23) possesses a high sense of involvement, Poblacion (3.90) expresses a significant involvement, and Baybay (3.30) exhibits an adequate level of involvement. However, there are limited levels of awareness of SDGs, with Barangay Poblacion reporting moderate awareness (2.79) while Libertad (2.48) and Baybay (2.45) exhibiting low levels of awareness. The findings highlight the need to implement policy interventions aimed at capacity-building efforts, institutional support or reinforcement, and quality improvement in technical assistance with simultaneous promotion of non-discriminatory involvement of marginalized sectors towards the more effective integration of Sustainable Development Goals into the development planning at barangay levels.